2005
DOI: 10.1128/cdli.12.12.1448-1450.2005
|View full text |Cite
|
Sign up to set email alerts
|

Unidirectional Suppression of Anaplasma phagocytophilum Genotypes in Infected Lambs

Abstract: Five-month-old lambs were simultaneously infected with different doses of two 16S rRNA genetic variants of Anaplasma phagocytophilum and thereafter followed for clinical observation and blood sampling. The result of the study indicates a unidirectional suppression of genotypes in infected lambs, at least during a certain period of an A. phagocytophilum infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 23 publications
1
24
0
Order By: Relevance
“…Nonetheless, although we considered that the approach that we used merely identified the major contributing sequence type of a potential guild of infecting A. phagocytophilum strains, the clarity of most of the sequence data obtained indicated that the characterized sequence type was the overwhelming contributor to the guild and therefore probably the most important in terms of transmission. Our observation of a single genotype dominating the community of A. phagocytophilum strains in the blood is in keeping with previous studies (29,33). However, our results also suggest that a dominant genotype does not remain so for long.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Nonetheless, although we considered that the approach that we used merely identified the major contributing sequence type of a potential guild of infecting A. phagocytophilum strains, the clarity of most of the sequence data obtained indicated that the characterized sequence type was the overwhelming contributor to the guild and therefore probably the most important in terms of transmission. Our observation of a single genotype dominating the community of A. phagocytophilum strains in the blood is in keeping with previous studies (29,33). However, our results also suggest that a dominant genotype does not remain so for long.…”
Section: Discussionsupporting
confidence: 82%
“…The repeated but sporadic detection of rickettsemia in our study, for example, as seen for msp4 sequence type A in lamb 6019, is in keeping with this pattern. However, other experimental studies have demonstrated that the kinetics described above can be disrupted if other infecting A. phagocytophilum strains are present (29,33). Given the number of msp4 sequence types encountered in our study, it is very likely that lambs were simultaneously infected with multiple A. phagocytophilum strains; hence, interstrain interactions, affecting the infection kinetics of each, would be expected.…”
Section: Discussionmentioning
confidence: 86%
“…Whether this is due to competition among Anaplasma species remains to be elucidated, although it has been shown that some Anaplasma genotypes can prevent the multiplication of other genotypes. This has been observed in A. marginale, A. ovis, and A. phagocytophilum (5,6,22). In addition, sequence analysis revealed that goats are the most likely potential hosts of A. marginale and Anaplasma species closely related to A. platys.…”
Section: Discussionmentioning
confidence: 93%
“…Recent studies indicate that hosts may be infected with several variants simultaneously, and that these variants behave differently and interact in the mammalian host (Stuen et al, 2005).…”
Section: Genetic Variantsmentioning
confidence: 99%